Quantifying the impacts of abrasion and bacterial transfer when fish are exposed to sand during a catch-and-release event. Issue 3 (1st October 2020) - Foster, RM; Childs, A-R; Brooks, M; Farthing, MW; Butler, EC; Potts, WM
Abstract : Best-practice guidelines to improve recreational fishers' handling during catch-and-release (C&R) events are critical to improve the conservation and management of fish stocks worldwide. While best-practice research is growing, there are knowledge gaps, with the effects of sand exposure on fish mucous membranes understudied. This study aimed to determine the effects of exposing a fish to sand during a C&R event. A total of 360 juvenile (48–137 mm TL) Cape stumpnose Rhabdosargus holubi were subjected to a simulated C&R event during which they were either held: (i) with wet hands, or (ii) dry hands; or with wet hands and then placed on either (iii) wet sterilised sand, (iv) dry sterilised sand, (v) wet unsterilised sand, or (vi) dry unsterilised sand. Fish were maintained in a recirculating system for two weeks, euthanised and subjected to an examination of their mucous layer (bacterial counts, abrasion counts and percentage of abrasion area) and an internal biological assessment. Bacteria from fish mucous layers were cultivated on agar plates to count bacterial colonies. Fish appeared to be healthy and mortality was low (2.5%) after the two-week treatment period. There were no significant differences in the number of skin abrasions among treatments. Although not significant, unsterilised-sand treatments had higher mean bacterial counts and large variation among individuals. Variation was attributed to abrasion and subsequent exposure to foreign bacteria in these treatments. Although the findings suggest that exposure to sand did not negatively affect fish health and survival, larger fish may be more susceptible to abrasions and infections.